2021
DOI: 10.1088/1757-899x/1070/1/012032
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fly ash and bottom ash on the ratio of splitting tensile strength to compressive strength of concrete

Abstract: The construction industry has suffers from extra ordinary utilization of cement and sand in all the part of globe. For overcome the future scarcity issue partial replacement to cement with option of fly ash material and fine aggregate or sand with bottom ash prove better solution. For this study, effect of different water cement ratio mainly 0.5, 0.55, 0.6 evaluated on binder content 300kg/m3 of concrete. f/c (fly ash/cement) ratio also taken into account with wide range as 0, 0.11, 0.25, 0.43, 0.67 and 1.0. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The samples containing the lowest fly ash content gave higher split tensile strength which was in contrast to what was noted for flexural strength. Several researchers [50][51][52][53][54][55] noted the same trend of reduction in concrete flexural strength with increase in fly ash content. This phenomenon can be attributed to the bond strength of the fly ash compared to the cement that it has replaced.…”
Section: Effect Of Pet and Fly Ash On Composite Split Tensile Strengthmentioning
confidence: 76%
“…The samples containing the lowest fly ash content gave higher split tensile strength which was in contrast to what was noted for flexural strength. Several researchers [50][51][52][53][54][55] noted the same trend of reduction in concrete flexural strength with increase in fly ash content. This phenomenon can be attributed to the bond strength of the fly ash compared to the cement that it has replaced.…”
Section: Effect Of Pet and Fly Ash On Composite Split Tensile Strengthmentioning
confidence: 76%
“…Since a cement composite's primary function as a construction material is compression, its mechanical strength is prized above all others. Studies have shown that ordinary compressive strengths are within the range of 25 to 115 MPa [45][46][47][48][49]72]. Generative ensemble approaches, on the other hand, produce groups of base learners that manipulate the base supervised learning or the data frame structure to enhance the base learners' variety and performance.…”
Section: Literature Reviewmentioning
confidence: 99%